2003
DOI: 10.3171/foc.2003.15.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after minimal-access surgery for recurrent lumbar disc herniation

Abstract: Object Experience with minimal-access surgical approaches for revision lumbar surgery has not been previously reported. Methods During a 7-month period, 10 consecutive patients with recurrent disc herniations underwent revision operations in which microendoscopic discectomy (MED) was performed. Perioperative data and clinical outcomes (according to Macnab criteria) were compared with those obtained in 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 17 publications
2
37
0
2
Order By: Relevance
“…33 The overall success rate of 90% in our series is comparable to reported success rates of MED and ETD in the literature. 1,7,14,15,24,25,32,39,43 The mean operative time of 90 ± 35 minutes is comparable to other series using MED (98-102 minutes). 15,24,25 The instability/fusion rate in our series was 6.7%.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…33 The overall success rate of 90% in our series is comparable to reported success rates of MED and ETD in the literature. 1,7,14,15,24,25,32,39,43 The mean operative time of 90 ± 35 minutes is comparable to other series using MED (98-102 minutes). 15,24,25 The instability/fusion rate in our series was 6.7%.…”
Section: Discussionsupporting
confidence: 67%
“…1,7,14,15,24,25,32,39,43 The mean operative time of 90 ± 35 minutes is comparable to other series using MED (98-102 minutes). 15,24,25 The instability/fusion rate in our series was 6.7%. In another series of 16 patients 43 and in two 10-patient series described by Le et al 24 and Isaacs et al 15 in 2003, no case of instability and fusion was reported.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations